Comparative study on optimal continuous positive airway pressure and predicted continuous positive airway pressure in obstructive sleep apnoea - K. K., Shyamala; Khatri, Bidhata; Suresh, Ashwin; Rajendran, Gokul (International Journal of Advances in Medicine, 2017)
Background: Continuous positive airway pressure (CPAP) is the first line non-invasive and safest treatment of obstructive sleep apnoea (OSA). Optimal CPAP therapy prescribed is obtained by manual titration in lab setting. Due to lack of data in Indian population predicted CPAP pressure proposed by Hoffstein is used using body mass index (BMI), neck circumference (NC) and apnoea-hypopnoea index (AHI) to correlate with the optimal pressure by automatic CPAP titration. Methods: The study was of retrospective and observational type. It included OSA patients diagnosed by overnight polysomnography (PSG) who had undergone automatic CPAP titration. The correlation of optimal pressure of automatic CPAP and predicted CPAP was studied. Results: A total of 30 patients were included in the study of which 23 were males and 7 were females. It was found that 28 patients had severe OSA and 2 had moderate OSA. AHI significantly improved (P = 0.000) with automatic CPAP titration. The mean CPAP predicted pressure (8.77±2.05) was found lower than the therapeutic optimal pressure (13.03±3.18) prescribed and the value exceeded the range ±2 in 76% of patients. Conclusions: Use of automatic CPAP limits the role for predicted formula for in lab titration/unattended home setting and patients who don’t undergo CPAP titration study, reducing the cost of testing. However, the predicted pressure could be used as a starting pressure for initiation of CPAP titration in lab setting for manual titration.